Neurophysiological mechanisms of pain and its quantitative assessment in endometriosis - Viktor V. Loginov; Alexander V. Vartanov; Semen A. Feigin; Stanislav V. Pavlovich (IP Berlin A.V., 2021)
The solution of many clinical problems, including the issues of the origin of pain as a component of individual pathologies, lies in the plane of quantitative objectification of the underlying disease and elucidation of the role of pain syndrome (PS) in it. The analysis of literature data on methods of pain assessment, including quantitative scales and questionnaires, biochemical and instrumental studies, was carried out. Various PS correlates used in fundamental and applied research are considered. The neurophysiological mechanisms of pain formation and specific methods for assessing PS in endometriosis were studied.